Risk of pain disorders in offspring of parents with substance use disorders. Issue 7 (13th April 2022) - Li, Dian‐Jeng; Chen, Mu‐Hong; Bai, Ya‐Mei; Tsai, Shih‐Jen; Cheng, Chih‐Ming; Su, Tung‐Ping; Chen, Tzeng‐Ji; Yeh, Ta‐Chuan; Liang, Chih‐Sung
Abstract : Aims: Individuals with substance use disorders (SUD) have higher risk of developing pain disorders. This study aimed to investigate the risk of major psychiatric disorders (MPD), SUD, and pain disorders among their offspring. Methods: This study used data from the Taiwan National Health Research Database. The case cohort included participants who had a parent diagnosed with SUD. The matched control cohort was offspring of parents without any SUD or major psychiatric disorder (MPD). Poisson regression was applied to estimate the risk of MPD, SUD, and pain disorder between case and control cohorts. Results: We recruited 13, 840 cases and 138, 400 matched controls. After adjusting for demographic characteristics and family history of psychiatric disorder, the offspring of parents with SUD had higher risk for bipolar disorder (reported as risk ratio with 95% confidence interval: 2.48, 1.79–3.43), depressive disorder (2.22, 1.94–2.52), SUD (2.53, 2.18–2.92), and alcohol use disorder (1.43, 1.16–1.76) than controls. With adjustments of demographic characteristics, individual MPD, and family history of psychiatric disorder, they also presented higher risk than controls for several pain disorders, including migraine (1.43, 1.15–1.78), fibromyalgia (1.21, 1.03–1.42), dorsopathies (1.20, 1.06–1.37), dysmenorrhea (1.16, 1.04–1.29), irritable bowel syndrome (1.26, 1.11–1.43), and dyspepsia (1.14, 1.02–1.27). Conclusions: Clinicians should be aware of the influence of parental SUD on the elevated risk for MPD, SUD, and pain disorders in their offspring.